On the approximation of functions from Weyl-Nagy classes by Zygmund sums in the L_q metric - Kostich, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
In the integral metric, estimates exact by order are found for deviations of the Zygmund linear means from functions, which belong to Weyl-Nagy classes.